Seasonal morphology of the domestic quail (Coturnix coturnix japonica) testis - Artoni, SMB; Orsi, A. M.; Carvalho, TLL; Vicentini, C. A.; Stefanini, M. A. (Blackwell Wissenschafts Verlag Gmbh, 1999)
A histological study was conducted on the testes of adult domestic quails (Coturnix coturnix japonica) over a year. The results revealed a clear variation of testicular weight, seminiferous tubule diameter, and the thickness and composition of the germinal epithelium over the year. The highest testicular weights were detected at the end of the autumn and during the winter (short-day period), reaching a maximum, together with spermatogenic activity, in September (long-day period in the southern hemisphere). In contrast, both testicular weight and spermatogenic activity were markedly decreased at the end of spring and during summer (long-day periods in the southern hemisphere).